2019
DOI: 10.1021/acs.jpcc.9b08084
|View full text |Cite
|
Sign up to set email alerts
|

Alkoxy Chain Number Effect on Self-Assembly of a Trigonal Molecule at the Liquid/Solid Interface

Abstract: We herein investigated the effect of the number of alkoxy chains on the two-dimensional selfassembly of a trigonal molecular building block. To this end, a dehydrobenzo[12]annulene (DBA) derivative, DBA-OC14-OC1 having three tetradecyloxy chains and three methoxy groups in an alternating manner, was synthesized. Scanning tunneling microscopy (STM) observations at the 1,2,4-trichlorobenzene (TCB)/graphite interface revealed that DBA-OC14-OC1 forms three monolayer structures, porous honeycomb, parallelogram, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…The translational entropy, on the contrary, would favor formation of large species like macrocycles and polymers, as they take more space on the surface, thus allowing small species to leave the surface and return in solution. However, to accurately estimate entropy of this reactive, multicomponent and structurally flexible/large molecular system, as compared to the current studies, , is still at an early stage and thus is beyond the scope of our work.…”
Section: Resultsmentioning
confidence: 99%
“…The translational entropy, on the contrary, would favor formation of large species like macrocycles and polymers, as they take more space on the surface, thus allowing small species to leave the surface and return in solution. However, to accurately estimate entropy of this reactive, multicomponent and structurally flexible/large molecular system, as compared to the current studies, , is still at an early stage and thus is beyond the scope of our work.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the alkylation of rigid molecules can alter their physical properties [1][2][3][4][5][6][7][8][9][10][11] significantly, including their thermal properties, [12][13][14][15] crystal structure, [16][17][18][19][20][21] and the structure of adsorbed monolayers. [22][23][24][25][26][27][28] We have analyzed the thermal properties of salen derivatives bearing alkyl chains of variable length and found that those with alkoxy groups adopt a liquid crystalline state at varying temperatures depending on the alkyl chain length. 29,30 In contrast, OC12-salpn, a salen derivative with a methyl group introduced as steric bulk, exhibited cold crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…10g In the latter case, the formation of D 6hsymmetric structures is a direct consequence of the synthetic strategies in which either six equal spoke-rim-segments are coupled to a central (arylene) hub (via Sonogashira reaction), 10a,b,d,f or symmetrical acetylenes are trimerized (via Vollhardt cyclization) 10g,15 before the rim is closed. While efforts have been made to study how the symmetry of 2D supramolecular tectons is related to the nanopatterns formed, 16,17 reducing the symmetry of the MSWs has not yet been described. Vollhardt acetylene trimerization of an unsymmetrical acetylene is a straightforward method to obtain such compounds.…”
Section: Introductionmentioning
confidence: 99%